It took me a while to solve this!

k = 0 m ( 2 n k k ) ( 2 n k n ) 2 n 4 k + 1 2 n 2 k + 1 2 n 2 k \large \sum_{k=0}^{m} \,\,\large \frac{{2n-k}\choose{k}}{{2n-k}\choose{n}} \cdot \ \frac{2n-4k+1}{2n-2k+1} \cdot \,2^{n-2k}

Given that n n is a positive integer and m m and n n are non-negative integers such that m n m \,\leq\, n , which of the given option is the closed form expression of given summation above.

( n m + 4 ) ( 2 n 2 m n m + 1 ) 2 n 2 m \frac{{n}\choose{m+4}}{{2n-2m}\choose{n-m+1}}2^{n-2m} ( n + 2 m ) ( 2 n 2 m + 2 n m + 1 ) 2 n 2 m \frac{{n+2}\choose{m}}{{2n-2m+2}\choose{n-m+1}}2^{n-2m} ( n m ) ( 2 n 2 m n m ) 2 n 2 m \frac{{n}\choose{m}}{{2n-2m}\choose{n-m}}2^{n-2m} ( n + 4 m + 7 ) ( 2 n 2 m + 9 n m + 6 ) 2 n 2 m \frac{{n+4}\choose{m+7}}{{2n-2m+9}\choose{n-m+6}}2^{n-2m}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
May 8, 2016

k = 0 m ( 2 n k k ) ( 2 n k n ) 2 n 4 k + 1 2 n 2 k + 1 2 n 2 k = k = 0 m n ! ( n k ) ! k ! ( 2 n 2 k ) ! 2 n 4 k + 1 2 n 2 k + 1 2 n 2 k = k = 0 m n ! ( n k ) ! k ! ( 2 n 2 k ) ! ( 1 2 k 2 n 2 k + 1 ) 2 n 2 k = k = 0 m { n ! ( n k ) ! k ! ( 2 n 2 k ) ! 2 n 2 k k n ! ( n k ) ! k ! ( 2 n 2 k + 1 ) ! 2 n 2 k + 1 } = k = 0 m n ! ( n k 1 ) ! k ! ( 2 n 2 k 1 ) ! 2 n 2 k 1 k = 1 m n ! ( n k ) ! ( k 1 ) ! ( 2 n 2 k + 1 ) ! 2 n 2 k + 1 = k = 0 m n ! ( n k 1 ) ! k ! ( 2 n 2 k 1 ) ! 2 n 2 k 1 k = 0 m 1 n ! ( n k 1 ) ! k ! ( 2 n 2 k 1 ) ! 2 n 2 k 1 = n ! ( n m 1 ) ! m ! ( 2 n 2 m 1 ) ! 2 n 2 m 1 = n ! ( n m ) ! m ! ( 2 n 2 m ) ! 2 n 2 m = ( n m ) ( 2 n 2 m n m ) 2 n 2 m \begin{array}{rcl} \displaystyle \sum_{k=0}^m \frac{\binom{2n-k}{k}}{\binom{2n-k}{n}}\, \frac{2n-4k+1}{2n-2k+1}2^{n-2k} & = & \displaystyle \sum_{k=0}^m \frac{n! (n-k)!}{k! (2n-2k)!}\,\frac{2n-4k+1}{2n-2k+1}\,2^{n-2k} \\ & = & \displaystyle \sum_{k=0}^m \frac{n! (n-k)!}{k! (2n-2k)!} \left(1 - \frac{2k}{2n-2k+1}\right)2^{n-2k} \\ & = & \displaystyle \sum_{k=0}^m \left\{ \frac{n! (n-k)!}{k! (2n-2k)!}\,2^{n-2k} - k\,\frac{n!(n-k)!}{k! (2n-2k+1)!}\,2^{n-2k+1}\right\} \\ & = & \displaystyle \sum_{k=0}^m \frac{n! (n-k-1)!}{k! (2n-2k-1)!}\,2^{n-2k-1} - \sum_{k=1}^m \frac{n! (n-k)!}{(k-1)! (2n-2k+1)!}\,2^{n-2k+1} \\ & = & \displaystyle \sum_{k=0}^m \frac{n! (n-k-1)!}{k! (2n-2k-1)!}\,2^{n-2k-1} - \sum_{k=0}^{m-1} \frac{n! (n-k-1)!}{k! (2n-2k-1)!}\,2^{n-2k-1} \\ & = & \displaystyle \frac{n! (n-m-1)!}{m! (2n-2m-1)!}\,2^{n-2m-1} \; = \; \frac{n! (n-m)!}{m! (2n-2m)!}\,2^{n-2m} \\ & = & \displaystyle \frac{\binom{n}{m}}{\binom{2n-2m}{n-m}}2^{n-2m} \end{array}

Nice solution. Does anyone know if there is a nice combinatorial argument for proving this?

Eli Ross Staff - 5 years, 1 month ago

Log in to reply

I'm also very eager to see such a solution.

Aditya Sky - 5 years, 1 month ago

Well done (+1) :).

Aditya Sky - 5 years, 1 month ago

I did the same thing. I messed up in the beggining. We have to be extremely cautious.

Srikanth Tupurani - 2 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...